First‐Principles Study of the 30° and 90° Partial Dislocations in HgTe, CdTe, and Hg0.7Cd0.3Te. Issue 11 (17th August 2022) - Hew, Nigel Lee En; Spagnoli, Dino; Faraone, Lorenzo
Abstract : The goals of this study are to use density functional theory to study the core structure energetics of the 30° and 90° partial dislocations in HgTe, CdTe, and Hg0.7 Cd0.3 Te as well as the density of states of these dislocations in CdTe and Hg0.7 Cd0.3 Te. For the 30° partial dislocations, two stable dislocation pairs were found. The pair with a double‐periodic α‐core (Te) dislocation and a single‐periodic β‐core (Hg/Cd) dislocation was found to be the most stable out of the two for the simulation sizes tested. For the 90° partial dislocations, two stable dislocation pairs were also found. The first has a single‐periodic β‐core dislocation and a single‐periodic α‐core dislocation, whereas the second has a double‐periodic β‐core dislocation and a single‐periodic α‐core dislocation. The most stable out of the two depends on the simulation size tested. For both of these partial dislocations in Hg0.7 Cd0.3 Te, it was found that it is energetically favourable for Hg atoms to segregate to the dislocation cores. Furthermore, in CdTe and Hg0.7 Cd0.3 Te, it was found that the 90° partial dislocations are likely to be more detrimental to the material optoelectronic properties since they introduce more mid‐gap states within the band gap in comparison to the 30° partial dislocations. Abstract : This paper includes work regarding density functional theory (DFT) studies undertaken on the 30° and 90° partial dislocations in HgTe, Hg0.7 Cd0.3 Te, and CdTe. The results include the dislocation core structures and energies as well as the impact that these dislocations have on the optoelectronic properties through the density of states.